Scenes from an Imaginary Country: Test Images and the American Color Television Standard. (January 2016) - Mulvin, Dylan; Sterne, Jonathan
American analog color television—so-called NTSC color—is likely the most pervasive image standard of the twentieth century, yet it is infamous for its technical shortcomings. Through a history and analysis of the National Television System Committee (NTSC) standard, this article argues that the political presuppositions of engineers shaped the representational capacities of television for nearly sixty years. In particular, the test images used to develop a perceptually satisfying image evince assumptions of a leisurely and white United States as the "normal" subject matter of television. In this way, test materials coalesce abstract assumptions about the normal and the exceptional at the level of both form and content. This article concludes that NTSC color served as a model for how normed cultural sensibilities about image quality, perceptual ability, and the representational imaginary have been built into subsequent technical standards. A Scalar version of this paper, with more pictures, is available athttp://colortvstandards.net